Patient outcomes after AF ablation using Ablation Index technology with oesophageal protection: insight from the IMPACT study. (25th November 2020) - Leung, L; Bajpai, A; Zuberi, Z; Li, A; Norman, M; Kaba, R; Akhtar, Z; Evranos, B; Gonna, H; Harding, I; Sohal, M; Al-Subaie, N; et al.
Abstract: Background: Atrio-oesophageal fistula formation accounts for the majority of AF ablation-related morbidity and mortality. Thermal injury to the oesophagus can be significantly reduced by application of oesophageal cooling for protection during AF ablation. The effect of this method of oesophageal protection in patients receiving radiofrequency (RF) ablation guided by Ablation Index technology is currently unknown. Objective: To investigate the ability of a temperature control device to protect the oesophagus from ablation-related thermal injury in patients receiving AF ablation guided by Ablation Index technology. Methods: The IMPACT study is a single-centre, prospective, double-blind randomized controlled trial, which investigated the ability of a controlled method of oesophageal cooling to protect the oesophagus from ablation-related thermal injury. The EnsoETM device was used to deliver oesophageal cooling. This method was compared in a 1:1 randomization to a control group of standard practice utilizing a single-sensor temperature probe. In the study group, the device was used to keep the luminal temperature at 4°C during RF ablation. All participants received AF ablation using Ablation Index technology at posterior and anterior settings (30W at 350–400 and 40W at 450–500, respectively). Endoscopic examination was performed within 7 days post-ablation and oesophageal injury was graded. The patient and the endoscopist were blinded to the randomization. Structured clinical follow up occurred after 3 months post-ablation; both patient and follow up clinician were blinded. Results: We recruited 188 patients, of whom 120 underwent endoscopic evaluation. Thermal injury to the mucosa was significantly more common in the control group than in those receiving oesophageal protection (12/60 versus 2/60; P=0.008). There was no difference between groups in RF time, lesion duration, force, power and combined ablation index (P value range= 0.2–0.9). Procedure and fluoroscopy duration were similar (P=0.97, P=0.91 respectively). The majority of those who passed through the 1st follow up evaluation (n=136) did not have gastrointestinal or chest pain symptoms post ablation and there was no difference between the randomized groups. Only 4.4% overall had severe symptoms and they were poorly correlated against those who sustained mucosal lesions. AF recurrence was similar in both groups (8% vs 8.8%). There were 2 cases of vascular trauma needing intervention in the control group and 1 case of conservatively managed pericardial effusion in the protected group only. Clinical and endoscopy findings did not report any EnsoETM device-related trauma. Conclusion: Thermal protection of the oesophagus significantly reduces ablation-related thermal injury compared to standard care when ablation is performed using radiofrequency with Ablation Index technology. This method of oesophageal protection is safe and does not compromise the efficacy of the ablation procedure. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): 1. Public hospital: St. George's NHS Foundation Trust; 2. Private company: Attune Medical (Chicago, IL)